2018
DOI: 10.1080/10986065.2018.1474532
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Mathematical Modeling Competencies: An Investigation of Prospective Secondary Mathematics Teachers

Abstract: A study with prospective teachers without prior mathematical modeling experience sheds light on how their newly developed conceptual understanding of modeling manifested itself in their work on the final task of a modeling module within a pedagogy course in secondary mathematics curriculum and assessment. The main purpose of the module was to provide opportunity for the prospective teachers to experience the Common Core Mathematical Practice Model with Mathematics and begin to develop competency in modeling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
5
25
0
1
Order By: Relevance
“…Therefore, they may know more about how specific modeling tasks should be analyzed compared to providing feedback. This explanation is supported by existing studies, which report PSTs' difficulties in suggesting alternative approaches (Anhalt et al, 2018).…”
Section: Discussion Of Mpck Of Mathematical Modelingsupporting
confidence: 68%
See 2 more Smart Citations
“…Therefore, they may know more about how specific modeling tasks should be analyzed compared to providing feedback. This explanation is supported by existing studies, which report PSTs' difficulties in suggesting alternative approaches (Anhalt et al, 2018).…”
Section: Discussion Of Mpck Of Mathematical Modelingsupporting
confidence: 68%
“…Earlier studies have reported similar findings. For example, as noted above, PSTs were typically found to experience difficulties at some stages of the mathematical modeling cycle, particularly at the stages of interpreting and validating (Anhalt et al, 2018;Tan & Ang, 2013).…”
Section: Discussion Of Mck On Mathematical Modelingmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study (Anhalt, Cortez, & Been Bennett, 2018) focused on the particular competency of making appropriate assumptions to construct a model. We designed problems that required multiple assumptions and analyzed students' work and their reflections on their work to determine when during the modeling process assumptions were made.…”
Section: For Permission To Reprint This Article Please Contactmentioning
confidence: 99%
“…Schematic of the progressive modeling cycle experienced by prospective teachers,Anhalt, Cortez, & Been Bennett, 2018. …”
mentioning
confidence: 99%